Effect of Tofu Dregs Flour Substitution and Tongkol Fish (Euthynnus affinis) on Patty Burger Quality - Muhammad Daiyan; Tengku Mia Rahmiati; Amri Amin (Serambi Journal of Agricultural Technology, 2020)
Tongkol fish and tofu dregs have protein that can replace as a beef so that they can be used as a filling for burgers. This research used a completely randomized design (CRD) 2 factorial that used was the addition of cob fish = 150 grams, 200 grams and 250 grams and the addition of tofu dregs flour = 40 grams, 60 grams and 80 grams. The best treatment chosen for the results of this study was the quality burger patty with chemical properties of 78.95% water content, 3.38% ash content, content protein 16.54%,  color organoleptic test 4.06 (likes), taste 4.00 (likes), texture 3.98 (likes), hedonic color  test 4.13 (brownish red), aroma 4.18 (moderate) , texture 3.90 (soft) and unpleasant aroma 3.15 (moderate).